Risk-Based Integration of Fault Mitigation Into Spatial Planning Land Dynamics and Settlement Vulnerability in Tanah Datar - Annisa; Binti Muhammad Yusoff, Safiah Yusmah; Febriandi; Ratna Wilis (Sumatra Journal of Disaster, Geography and Geography Education, 2026)
Tanah Datar Regency is highly vulnerable to earthquake hazards due to the Semangko fault and its two active segments, Sumani and Sianok, which induce significant tectonic deformation and directly affect settlements and land-use dynamics. This study was conducted to fill the knowledge gap related to the integration of disaster mitigation in spatial planning, with two main objectives: 1) identifying and analyzing spatial conflicts that arise between the dynamics of land use change, the distribution of vulnerable settlements, and active fault disaster prone zones with the regional spatial planning of Tanah Datar Regency; and 2) formulating a model for integrating fault disaster mitigation into spatial planning based on risk analysis as a recommendation for sustainable spatial planning policies. The approach used is a mixed method with sequential explanatory variables. Quantitative analysis was conducted through spatial mapping to assess hazard levels, physical vulnerability, and the dynamics of land-use change, while qualitative analysis was used to validate the model and policy through regulatory interpretation and stakeholder interviews. The results show that 7.59% of Tanah Datar is in a high earthquake-hazard zone, followed by moderate (15.9%) and low (1.45%) hazards. Population distribution also shows that the majority of the population (20,094) lives in areas with a high level of impact, while 58,230 people are in the medium category and 67,87 people in the low category. This finding confirms the mismatch between settlement Development, land conversion dynamics, and the risk zoning applicable in the spatial plans. Therefore, the integration of disaster mitigation can no longer be positioned as an additional compent, but must become the primary foundation in spatial planning. This study recommends an integration model that places disaster risk maps as the primary reference in the formulation of spatial policies, thereby guiding the establishment of protected zones, settlements, and economic centers more safely and sustainably. This guide is expected to strengthen regional resilience and provide a scientific basis for the Development of evidence-based spatial planning policies.